Sustainable School Financial Education: a possibility in the Early Years of Elementary School - Barbara Cristina Mathias dos Santos; Alexandre Lopes de Oliveira (Educação Matemática Debate)
School Financial Education is a subject that has yet to be widely disseminated in Brazil, although indicated in official documents. That said, there is a lack of material aimed at children. This research is justified by proposing a Teaching Guide that seeks to respond to the problem of how to work on Sustainable School Financial Education in the Early Years of Primary School. This paper aims to present the results of a doctoral research project that looked at the value of things, the fundamental and the superfluous, ethics, economics, and sustainability. The methodological approach applied was Didactic Engineering. The main result was confirmation of the hypothesis that students aged between 7 and 9 can work on the themes and put their learning into practice.